IMC education and digital disruption. (10th April 2017) - Kerr, Gayle; Kelly, Louise
Abstract : Purpose: The purpose of this paper is to benchmark the progress of integrated marketing communication (IMC) education, by replicating and extending a study on IMC education by Kerr (2009). It documents progress, examines the impact of digital disruption and concludes with an agenda for change. Design/methodology/approach: Using the Delphi technique, this study recruited leading IMC educators and thought leaders internationally to find consensus on an important range of IMC issues, including its place within the university, the IMC brand, curriculum, impact on practice, the incorporation of digital and future challenges. Findings: IMC has strengthened its place within the university and also within the minds and understanding of academics, students and industry. Digital disruption provides many challenges including updating curriculum and up skilling staff. It is vital, however, that IMC thinking be positioned as the integrator and digital as the facilitator, providing platforms to actualise IMC strategy such as content, customer service and cross-functional planning. Practical implications: This study shows what IMC education has achieved since Kerr's (2009) study. Further, it outlines what needs to be achieved in the future by providing a "To do" list for IMC educators. Originality/value: It is vital that the development and progress of this important new area of study is tracked to ensure industry challenges are met, such as digital disruption, and the right education for IMC managers of the future is provided.